Breast Cancer Screening Practices and Satisfaction With Healthcare Providers in Chinese Women: A Cross-sectional Study. Issue 2 (16th March 2022) - Zhang, Xuehui; Li, Ping; Zhang, Chunmiao; Guo, Pingping; Wang, Jie; Liu, Na; Yang, Shu; Yu, Lin; Zhang, Wei
Abstract : Background: The Chinese government has proposed cancer screening guidelines and launched 2 cancer screening programs to improve screening practices. However, the screening participation rates of Chinese women remain low. Exploring the factors affecting breast cancer screening to promote cancer screening is necessary. Objective: The aim of this study was to investigate women's satisfaction with healthcare providers and screening practices. Methods: A cross-sectional survey was conducted from November 2019 to April 2020 in Changchun, Jilin Province, China. The Medical Care Satisfaction Scale and SERVQUAL were used to quantify women's satisfaction with doctors and nurses, respectively. Results: Women's satisfaction with doctors (68.81 ± 11.08; range, 20–100) and with nurses (87.64 ± 16.17; range, 22–110) was moderate. Compared with women who had not participated in screening within the past 2 years, screened women reported higher satisfaction with doctors ( P = .026) and nurses ( P = .012). Older age ( P = .004) was an independent predictor of women's satisfaction with doctors. Similarly, women's education level ( P = .049), chronic disease history ( P = .029), and physical examination history ( P = .039) were 3 independent predictors of women's satisfaction with nurses. Conclusions: Future intervention strategies can not only increase the screening rates by providing existing intervention methods but also improve women's satisfaction with healthcare providers to promote screening practices. Implications for Practice: This article provides a theoretical basis for healthcare providers to increase female screening practices. It also provides references for improving existing intervention methods.